2014
DOI: 10.5897/ajmr2013.6186
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of ringworm caused by Trichophyton verrucosum in a group of calves in Vom, Nigeria

Abstract: An outbreak of ringworm in young calves is reported from Vom in Nigeria. Twelve out of fourteen calves were observed to have skin lesions consistent with dermatophytosis. Lesions were seen mostly around the eyes and neck. Skin scrapings were collected from the affected areas and processed for mycology. Trichophyton verrucosum was isolated from all the affected calves. This study has shown that T. verrucosum can be a problem to watch for in calves in this particular environment, both as a zoonosis and economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 13 publications
6
20
2
2
Order By: Relevance
“…In the present investigation, the clinical diagnosis was confirmed by direct microscopy of dermatophyte in cutaneous lesions and by cultural isolation of T. verrucosum on mycological media. This observation is in conformity with the findings of other investigators [5,8,10]. Dermatophytosis is mainly encountered in calves [8,10,12].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In the present investigation, the clinical diagnosis was confirmed by direct microscopy of dermatophyte in cutaneous lesions and by cultural isolation of T. verrucosum on mycological media. This observation is in conformity with the findings of other investigators [5,8,10]. Dermatophytosis is mainly encountered in calves [8,10,12].…”
Section: Discussionsupporting
confidence: 82%
“…This observation is in conformity with the findings of other investigators [5,8,10]. Dermatophytosis is mainly encountered in calves [8,10,12]. However, the current study indicated that adult animal can also be affected with T.verrucosum.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations